CLOUD COMPUTING WEB-BASED LMS: INTERACTIVE LEARNING MEDIA TO ENHANCE STUDENTS' ACCOUNTING PARTICIPATION AND SKILLS - Octavianto, Said Nur; Santoso, Jarot Tri Bowo; Arief, Sandy; Baswara, Satsya Yoga (Assets: Jurnal Akuntansi dan Pendidikan, 2024)
ABSTRACT The need for more competitiveness among high school students can be attributed to the dearth of interactive learning media. This study aims to assess the efficacy of integrating LMS-based Cloud Computing Web Media with a scientific approach to enhance student engagement and accounting proficiency. Adopting a quantitative methodology with a quasi-experimental design, the study employs Class XII IPS 1 (the experimental class) and Class XII IPS 2 (the control class) as the sample set. The data collection techniques and instruments utilized pre-tests and post-tests in the form of HOTS-based multiple choice. The data analysis techniques employed the t-test, which included the Independent Samples t-test and paired Samples t-test, and was supported by the N-Gain Test. This study asserts that LMS-based cloud computing web media integrated with a scientific approach is effective in increasing student participation and accounting skills. Future research may develop LMS-based cloud learning media presented in the form of a website to support online accounting practicum learning. ABSTRAK Daya saing siswa SMA yang rendah disebabkan oleh kurangnya pemanfaatan media pembelajaran interaktif. Penelitian ini berupaya menganalisis efektivitas penggunaan Media Cloud Computing Web berbasis LMS terintegrasi pendekatan saintifik untuk meningkatkan partisipasi dan keterampilan akuntansi siswa. Penelitian ini menggunakan pendekatan kuantitatif dengan metode eksperimen semu (quasi experiment). Sampel yang ditetapkan yaitu Kelas XII IPS 1 (kelas eksperimen) dan Kelas XII IPS 2 (kelas kontrol). Teknik dan instrumen pengumpulan data menggunakan pre test dan post test berupa pilihan ganda berbasis HOTS, sedangkan teknik analisis data menggunakan Uji t yang mencakup Independent Samples t-Test, Paired Samples t-Test, dan didukung oleh Uji N Gain. Penelitian ini menyatakan Media Cloud Computing Web berbasis LMS terintegrasi pendekatan saintifik efektif untuk meningkatkan partisipasi dan keterampilan akuntansi siswa. Penelitian selanjutnya dapat mengembangkan media pembelajaran Cloud berbasis LMS yang dihadirkan dalam bentuk web (website) untuk menunjang pembelajaran praktikum akuntansi online.